ANALISIS RISIKO DALAM ALIRAN SUPPLY CHAIN PADA PROYEK KONSTRUKSI GEDUNG DI BALI - Kadek Aditya Dei; G.A.P. Candra Dharmayanti; N. Martha Jaya (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2017)
Abstract: Contruction project is began by the necessity of the owner who than passed on to other parties such as consultant, contractor, sub-contractor, supplier, labour that are interlinked into a chain of construction project . The relationship between these parties put contractor as the chain in this relationship, known as construction supply chain (CSC). In CSC there are possibilities of risks that can increase the project cost, thus impact on the declining of the contractor’s profit. These source from three flows of supply chain system, that is flow of informations, flow of material and flow of funds. This research aims to analysis the supply chain risks on building construction project in Bali that affect on the declining of contractor’s profit. Data was collected using a questionnaire survey. The respondents were selected based on purposive sampling method, covers the experst on building construction projects. The method of analisys covers risk assement and linear regression analysis. The risk assement analysis shows that there are 26 major risks (6 risk in flow of information, 16 risks in flow of material and 4 risks in flow of fund). The regression analysis suggests that risks sourced from flow of informations is the most significant factor that increase the projects cost, therefore mitigating focused on the flow of information with develop project’s administration as shop drawing, work permits, material’s approval, completeness of contract and daily coordination.